Efficacy and safety of sacubitril/valsartan on postoperative atrial fibrillation in adult patients undergoing cardiac surgery: a real-world observational study - Chen, Xiaodong; Liu, Pengxin; Zhu, Fengzheng; Wang, Dong; Yang, Sumin; Yan, Wenlong (Frontiers in Cardiovascular Medicine, 2024)
BackgroundThe mechanism underlying new-onset postoperative atrial fibrillation (POAF) in adult cardiac surgery is not well understood. However, efficient pharmacological methods to prevent and treat arrhythmic complications are still lacking. In the present study, we explored the efficacy and safety of sacubitril/valsartan (sac/val) in the control of POAF in adult cardiac surgery patients.MethodsBetween January 2021 and December 2021, 667 eligible adult patients who underwent cardiac surgery at the Affiliated Hospital of Qingdao University were enrolled. The participants were divided into two groups according to whether sac/val was used: the sac/val group (N = 101) and the control group (N = 566). The main observational endpoints were the incidence of POAF, left ventricular ejection fraction (LVEF) recovery, in-hospital mortality, and short-term mortality.ResultsPatients in the sac/val group had a lower incidence of POAF than those in the control group (26/101 vs. 204/566, P = 0.045). Patients in the sac/val group also showed a higher communicative risk for POAF incidence using the Kaplan–Meier survival analysis. In addition, patients in the sac/val group showed better LVEF recovery, with dynamic changes in LVEF superior to that of the control group. The change in LVEF in the sac/val group was 1.78 ± 5.41, compared with −1.19 ± 10.92 in the control group (P = 0.008).ConclusionsThis is the first observational study to evaluate the efficacy and safety of sac/val in the prevention and treatment of POAF after cardiac surgery. The results demonstrated that compared with patients who did not receive sac/val treatment, those who received Sac/val treatment showed better POAF control and LVEF recovery. These results should be cautiously interpreted and further confirmed using larger sample sizes and prospective randomized controlled trials.